Analysis of Inpatient Care Utilization Among Type 2 Diabetes Mellitus Patients - Nauri Anggita Temesvari; Husni Abdul Muchlis (Universitas Duta Bangsa Surakarta, 2026)
Globally and in Indonesia, diabetes mellitus (DM) is mainly type 2. When outpatient care fails to control blood glucose, hospitalization treatment becomes necessary. This is in line with the implementation of the referral system in the era of the National Health Insurance. This study aims to analyze the utilization of hospitalization among patients diagnosed with Type 2 DM (T2DM). A cross-sectional design was applied using sample data from BPJS Kesehatan Year 2024, representing 2023 visit records. All patients admitted with T2DM were included. Inpatient utilization measured by admission frequency, intervals, length of stay, referral sources, diagnostic consistency, discharge status, and comorbidities among T2DM patients. Descriptive analysis was performed on patient characteristics and hospitalization utilization patterns. In 2023, there were 480 admissions involving 417 patients, mean interval between hospitalizations was 69 days. The length of hospital stay increased with the presence of complications. Most referrals came from hospitals, 66% of primary diagnoses matched the admission diagnosis, and hypertension was the most common comorbidity. Most discharge status was recovered. Recommendations include enhancing continuity of care and the referral back program through system integration to mitigate T2DM readmission risks.